(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
When it comes to helping out vulnerable people, places like old age homes and orphanages are essential. However, the sustainability of these institutions is often threatened by overreliance on unpredictable donor contributions. This study explores sustainable investment strategies for orphanages and old age homes aimed at minimizing reliance on donor funding. With growing financial constraints and fluctuating donations, these institutions must adopt innovative revenue-generating projects and strategic partnerships to ensure long-term sustainability while maintaining quality care. The research identifies key investment approaches, evaluates their effectiveness, and provides recommendations for successful implementation.